Antisemitism/ Antijudaism (Christian Ethics) - Koch, Elisa (SysLex, 2026)
The culmination of modern antisemitism in the Shoah represented not only a turning point for Jewish life in Europe and worldwide but also for Christian theological ethics. Against the backdrop of Theodor Adorno’s "new categorical imperative", criticism of antisemitism must become an integral part of Christian theological ethics. Post-Shoah Christian theology has offered promising metaethical approaches for this purpose. Intersectional approaches to theological ethics offer a further point of reference, as the power relations of antisemitism are currently receiving increasing attention in intersectional debates.